(untitled) (Research, Society and Development, 2022)
This study aims to analyze the evidence in the literature about the perception and paternal support in breastfeeding; to analyze triggering factors for early weaning related to the lack of paternal participation in the breastfeeding process; paternal participation in breastfeeding and its benefits to mother and baby. This is an integrative literature review carried out in the databases of the Virtual Health Library, Lilacs, Scielo, Medline and BDENF, which included publications from 2017 to 2021. The final sample consisted of 13 articles, being refined from one thorough reading. It is concluded that the active participation of the father in the breastfeeding process is extremely relevant, as the woman becomes susceptible to interruption of breastfeeding in the face of difficulties. The researched literature shows that many men have the perception that their support is essential for the continuity of breastfeeding, but the lack of knowledge on how to help women and participate in this process is a barrier that promotes their absence, in addition to the culture that affirms that breastfeeding it is an exclusive act of the woman. Thus, these men should be included in prenatal care so that they can be taught how to take care of the child and be supportive of breastfeeding.